The Systems Polyethylene and Polypropylene – CNTs Nanofillers: Quantum-chemical Modeling and Experimental Characteristics - Sementsov, Yu.I.; Tang, Hao; Wang, Dongxing; Demianenko, E.M.; Terets, M.I.; Ivanenko, K.O.; Ignatenko, O.M.; Makhno, S.M.; Sigareva, N.V.; Zhuravskyi, S.V.; et al. (Physics and Chemistry of Solid State, 2024)
The purpose of this work was to investigate the interaction of graphene-like nanoclusters with fragments of polymers of the same nature, but of a slightly different structure, for example, polyethylene (PE) and polypropylene (PP), experimentally and using quantum chemistry methods. It is experimentally shown that the reinforcement of PE and PP with carbon nanotubes (CNTs) by mixing in the melt, previously distributed from a stable aqueous dispersion on the surface of the polymer powder, leads to a change in structural, mechanical and thermodynamic characteristics.The degree of crystallinity changes, and the coherent scattering domain (CSD) size, the fracture stress increases, the fracture deformation, thermodynamic characteristics change, and such changes in characteristics for the PP-СNTs system prevail in comparison with the PE-CNTs system. The interaction energy of graphene-like fragments with PE and PP oligomers was calculated. It was established that the energy of interaction of a graphene-like nanocluster with a PP oligomer is greater, compared to PE, which is consistent with experimental data on the melting temperatures of pure polymers and polymer composites with nanotubes. The polymer with the surface of the nanocarbon fragment forms an intermolecular complex that is not covalently bound but is held by intermolecular dispersion forces.